2008
DOI: 10.1016/j.icarus.2007.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Cassini UVIS observations of the Io plasma torus

Abstract: On January 14, 2001, shortly after the Cassini spacecraft's closest approach to Jupiter, the Ultraviolet Imaging Spectrometer (UVIS) made a radial scan through the midnight sector of Io plasma torus. The Io torus has not been previously observed at this local time. The UVIS data consist of 2-D spectrally dispersed images of the Io plasma torus in the wavelength range of 561Å-1912Å. We developed a spectral emissions model that incorporates the latest atomic physics data contained in the CHIANTI database in orde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
193
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(209 citation statements)
references
References 104 publications
(106 reference statements)
13
193
2
Order By: Relevance
“…From Table 1, the expected dense regions in the plasma torus varies in different HST observation epochs. The results confirm the azimuthal variation of plasma density in the plasma torus, which was directly measured by Steffl et al (2008).…”
Section: Discussionsupporting
confidence: 86%
“…From Table 1, the expected dense regions in the plasma torus varies in different HST observation epochs. The results confirm the azimuthal variation of plasma density in the plasma torus, which was directly measured by Steffl et al (2008).…”
Section: Discussionsupporting
confidence: 86%
“…The S III line at 680 Å is by far the most energetic feature in the EUV spectrum of the torus. The general shape of the profile observed by EXCEED is fairly similar to the UVIS profile by the Cassini spacecraft (Steffl et al 2004a(Steffl et al , 2004b; however, our spectral image seems thinly. The weak emissions, e.g.…”
Section: First Images Of Jupiter and Venussupporting
confidence: 69%
“…More than 1000 kg of neutral gases from Io's atmosphere are ionized per second and produce a dense (approximately 2000 cm −3 ) torus of electrons, sulfur, and oxygen ions, trapped in Jupiter's strong magnetic field. While in situ measurements of the Io plasma torus by the Voyager and Galileo spacecraft (Frank and Paterson 2000;Bagemal 1985) and remote-sensing observations from the ground and from space-based UV telescope have characterized the density, temperature and composition of the plasma as well as the basic structure (Broadfoot et al 1981;Steffl et al 2004aSteffl et al , 2004bThomas et al 2003), the temporal variability of the torus remains poorly determined.…”
Section: First Target: Jupitermentioning
confidence: 99%
See 1 more Smart Citation
“…For example: the OI emission multiplets at 130.4 nm and 135.6 nm seen at both Earth and Ganymede can also be observed at Europa (Hall et al 1995;, Io (Ballester et al 1987;Clarke et al 1994;Roesler et al 1999) and Enceladus (Zastrow et al 2012); SI emissions at 129.9 nm, 138.9 nm, 142.9 nm and 147.9 nm are seen at Io (Ballester et al 1987;Roesler et al 1999); and N 2 LBH band emissions have been observed at Titan (Broadfoot et al 1981;Strobel and Shemansky 1982;Ajello et al 2008;Stevens et al 2011;Ajello et al 2012) and are predicted to exist at Triton (Strobel et al 1991). The Io torus also emits in the FUV region, with SII, SIII and SIV emissions dominating the spectrum (A Cassini UVIS spectrum is shown in Steffl et al 2004). As with Ganymede, several of these objects exhibit variable emission morphologies for various reasons.…”
Section: Discussionmentioning
confidence: 99%